Spatial Factors Influence Arithmetic Performance: The Case of the Minus Sign. Issue 8 (August 2014) - Jiang, Matthew J.; Cooper, Jennifer L.; Alibali, Martha W.
Spatial features of mathematical equations may influence how people solve and interpret those equations. This study examined whether manipulations of spatial features affected how participants solved and interpreted equations involving the minus sign. Undergraduate participants ( N = 91) solved multioperation arithmetic equations involving addition, subtraction, and multiplication (e.g. 25 − 3 + 2 × 5 = __). We varied the spacing of the final three operands and the position of the first operator relative to the adjacent operands. Participants also generated a story problem to correspond with a given equation. We evaluated the procedures that participants used in solving the equations by analysing both their solutions and their written work. Both close spacing of the final three operands and position of the first operation sign influenced the procedures that participants used. Both of the spatial manipulations also influenced participants' interpretations of the conceptual structure of the equations, as revealed in the story problems that they generated. These results have implications for understanding how people process mathematical symbols and for mathematics education.